2020
DOI: 10.1021/acs.chemmater.9b03765
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Critical Role of Ti Substitution in P2-NaxLiyMn1–yO2 Cathodes for Highly Reversible Oxygen Redox Chemistry

Abstract: Monovalent Li-substitution has been proven to be an effective strategy to resolve the pivotal problems confronted with P2-type layered Mn oxides, such as cooperative Jahn–Teller distortions of Mn3+ ions and drastic P2-(OP4)-O2 phase transformations occurring during desodiation. However, the cycling stability of most Li+-substituted P2-Na x Li y Mn1–y O2 remains far from satisfactory. We herein develop a facile Ti-substitution method to improve the cyclability by taking Na0.72Li0.24Mn0.76O2 (NLMO) as an example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 55 publications
4
83
1
Order By: Relevance
“…According to previous studies, the disorder in TM layers induced by low crystallization causes severe voltage decay and capacity reduction [14,46] because TM migration and irreversible slab gliding occur [46] . However, TM disordering caused by the substitution of d 0 (or d 10 ) ions not only eliminates the localized energy difference in Na sites but also increases reversibility [47–50] . Because d 0 and d 10 ions such as Ti 3+/4+ , Zn 2+ , Mg 2+ , and Li + are not electrochemically active in Na intercalation compounds, the structural variability that occurs during the redox of the TM−O orbital is reduced.…”
Section: Fundamental Science and Theories Of Anionic Redox In Cathodementioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, the disorder in TM layers induced by low crystallization causes severe voltage decay and capacity reduction [14,46] because TM migration and irreversible slab gliding occur [46] . However, TM disordering caused by the substitution of d 0 (or d 10 ) ions not only eliminates the localized energy difference in Na sites but also increases reversibility [47–50] . Because d 0 and d 10 ions such as Ti 3+/4+ , Zn 2+ , Mg 2+ , and Li + are not electrochemically active in Na intercalation compounds, the structural variability that occurs during the redox of the TM−O orbital is reduced.…”
Section: Fundamental Science and Theories Of Anionic Redox In Cathodementioning
confidence: 99%
“…Because d 0 and d 10 ions such as Ti 3+/4+ , Zn 2+ , Mg 2+ , and Li + are not electrochemically active in Na intercalation compounds, the structural variability that occurs during the redox of the TM−O orbital is reduced. In addition, the larger ionic radii of these species result in more effective diffusion paths for alkali metal ions, thereby increasing the ionic conductivity of the layered structure [50] . The substitution of TMs, which can increase covalency by donating electrons to TM−O bonds, is, thus, a good strategy to regulate the anionic redox activity and provide additional cation‐redox couples [49,51–53] .…”
Section: Fundamental Science and Theories Of Anionic Redox In Cathodementioning
confidence: 99%
“…The continuous reduction of the a-axis parameter was also indicative of the gradual oxidation from O 2− to O n− (n < 2) during charge, compensating for the charge imbalance occurring in Mn 4+ . Li et al [24] observed the migration of lithium using NMR in Na 0.72 [ [20]. However, the aforementioned P2 Na x [Li y Mn 1-y ]O 2 compounds exhibited hysteresis between charge and discharge, as evident in Figure 2(a).…”
Section: Sodium-deficient Layered Structuresmentioning
confidence: 99%
“…for which a third of the TM layers can be filled by mono-or divalent elements such as Li [17][18][19][20][21][22][23][24][25][26][27][28][29], Mg [46][47][48][49][50][51][52][53][54][55][56], and Zn [57][58][59] to induce an average oxidation state of Mn of 4+. Hence, the extraction of sodium ions in the structure is not theoretically possible because of the difficulty of the oxidation of Mn 4+ to higher valence states in an octahedral environment, in which the electrolyte does not decompose.…”
Section: Sodium-deficient Layered Structuresmentioning
confidence: 99%
See 1 more Smart Citation